2023
DOI: 10.1002/ird.2911
|View full text |Cite
|
Sign up to set email alerts
|

Computational fluid dynamics and artificial neural networks for modelling lined irrigation canals with low‐density polyethylene and cement concrete liners

Mohamed Galal Eltarabily,
Mohamed Kamel Elshaarawy,
Mohamed Elkiki
et al.

Abstract: This study numerically investigated the lining effect on the discharges and seepage losses of five reaches which belong to the El‐Sont Canal, Asyut, Egypt, using FLOW‐3D and Slide2 models, respectively. Two lining materials were considered, cement concrete (CC) and CC with low‐density polyethylene (LDPE) film. A cost analysis was performed to explore the feasibility of the proposed lining materials. Moreover, a parametric study was conducted by the Slide2 model to investigate the effect of canal geometry and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Results showed that 99.8% of the seepage discharges can be saved if the soil is highly compacted. Eltarabily et al (2023a) utilized the FLOW-3D and Slide2 models to estimate the discharge and seepage loss from the canal reaches, respectively. Moreover, the effect of lining on the discharge and seepage loss of the El-Sont Canal in Egypt was investigated using Cement Concrete (CC) and CC with Low-Density Polyethylene (LDPE) film.…”
Section: Introductionmentioning
confidence: 99%
“…Results showed that 99.8% of the seepage discharges can be saved if the soil is highly compacted. Eltarabily et al (2023a) utilized the FLOW-3D and Slide2 models to estimate the discharge and seepage loss from the canal reaches, respectively. Moreover, the effect of lining on the discharge and seepage loss of the El-Sont Canal in Egypt was investigated using Cement Concrete (CC) and CC with Low-Density Polyethylene (LDPE) film.…”
Section: Introductionmentioning
confidence: 99%